2002
DOI: 10.5210/fm.v7i8.975
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Challenges in Networked Learning: Hard Technologies Meet Soft Skills

Abstract: This paper gives an account of themes that emerged from a preliminary analysis of a large corpus of electronic communications in an online, mediated course for intercultural learners. The goals were to test assumptions that electronic communication is internationally standardized, to identify any problematic aspects of such communications, and to construct a framework for the analysis of electronic communications using constructs from intercultural communications theory. We found that cyberspace itself has a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 1 publication
1
36
0
1
Order By: Relevance
“…Several researchers have reported that cultural and language differences can effect online interactions and communications between students from different cultural backgrounds [26], [27]. In this study, the qualitative analysis of the open-ended question data indicated that this was so for only a minority of the Malaysian students.…”
Section: H Issues With Different Cultural Backgroundsmentioning
confidence: 86%
“…Several researchers have reported that cultural and language differences can effect online interactions and communications between students from different cultural backgrounds [26], [27]. In this study, the qualitative analysis of the open-ended question data indicated that this was so for only a minority of the Malaysian students.…”
Section: H Issues With Different Cultural Backgroundsmentioning
confidence: 86%
“…Students in face-to-face classroom settings see and work with one another and get to know each other well through the learning process. Online communications, on the other hand, lack elements inherent in face-to-face communication including context perception, eye contact, and a parallel visual and gestural information; the value of those elements is strongly embedded in some cultures, including the Confucian heritage cultures (Chase, Macfadyen, Reeder, & Roche, 2002). While for successful delivery online, the learning process on the Web needs to be well facilitated, the facilitation has to be particularly thoughtful when designing and delivering online programs to culturally diverse learners (Kum, Chang, & Bauer, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined differences across cultures (Cronje, 2011;Chew & Yee, 2015;Grandon et al, 2005;Li & Kirkup, 2005;Popov et al, 2012;Popov, Noroozi, Barrett, Biemans, Teasley, Slof & Mulder 2014;Zhu, Valcke & Schellens., 2009) and within cultures (Adler et al, 2001;Chase et al, 2002;Hamdan, 2014;Okwumabua, Walker, Hu & Watson, 2010). In a recent cross-cultural comparison between Malaysian and Australian students, no significant differences in students' perceptions existed on computer usage, lecturer support, equity, student interaction and collaboration (Chew & Yee, 2015).…”
Section: What Do We Know About Cultural Perceptions About Online Educmentioning
confidence: 99%
“…Cyberspace has a culture and gaps can exist between individuals as well as between individuals and the dominant cyber-culture, which increases the likelihood of miscommunication (Chase et al, 2002). The lack of elements found in FTF communication acerbates the intercultural communication online by limiting opportunities to give and 'save face' as well as draw meaning from nonverbal cues (Chase et al, 2002). The lack of contextual cues can inhibit students -particularly collectivist students, which may benefit from adding video or voice connection activities to online capabilities (Popov et al, 2014).…”
Section: What Do We Know About Cultural Perceptions About Online Educmentioning
confidence: 99%
See 1 more Smart Citation